The Impact of Direct Feedback on Students’ EFL Writing Skill: A Case Study on Writing III Course in STKIP Suar Bangli - I Putu Suyoga Dharma; Nirmala Tari (Universitas Pendidikan Ganesha, 2017)
This case study research aims at knowing the impact of direct feedback on EFL students‟ writing skill. This research was done on the fourth semester students of English Education Department in STKIP Suar Bangli. Totally, there were three students selected to be the subject. The students were assigned to write short essay consisting of 6-7 paragraphs, then it was returned after direct feedback was given. Next, the students were assigned to write the new one. It was then analyzed qualitatively. Based on the result of data analysis, it was discovered that there was no significant impact of direct feedback on students‟ writing quality. The students still made the same mistakes as before. It implies that the use of direct feedback should be reduced in writing.